RELASI KUASA DALAM NOVEL ANAK RANTAU KARYA AHMAD FUADI : KAJIAN TEORI MICHEL FOUCAULT - Ayuningtiyas, Ratna (sarasvati, 2019)
This study attempts to describe relation power and representation of relation power in a novel the Anak Rantau by ahmad fuadi, also describe media power. Dispersal device types of data used in this research is qualitative data. The subject of this research is a novel the Anak Rantau by ahmad fuadi. This study focused on problems associated with my counterparts power. The data obtained by read and noted Technique. Data analyzed by qualitative description technique. The validity of the data obtained through validity and reabilitas. The result showed that: ( 1 ) relation power in a novel Anak Rantau is for ever thinking and upper body. Types of relationships power over the thought of objectification, manipulation , domination stigmatization of, and control.Types of relationships power over the body of the form of objektive, manipulation and control, (2) there is dispersal device media, religion of power cultural and educational institutions.